Overexpression of phosphatidylethanolamine N-methyltransferase 2 in CHO-K1 cells does not attenuate the activity of the CDP-choline pathway for phosphatidylcholine biosynthesis. - Lee, M W (1996)
Chinese hamster ovary (CHO) cells express only a trace amount of phosphatidylethanolamine N-methyltransferase (PEMT) activity. CHO cells make their phosphatidylcholine (PC) via the CDP-choline pathway. We investigated whether or not overexpression of PEMT2, an isoform of PEMT, in these cells would down-regulate the activity of the CDP-choline pathway. Transfection of CHO cells with PEMT2 cDNA behind the cytomegalovirus promoter resulted in a series of cell lines that overexpressed PEMT2. Phospholipid metabolism was characterized in cell lines that expressed a medium (281 pmol/min per mg of protein) and a high (1300 pmol/min per mg of protein) level of PEMT activity. The expression of the regulated enzyme (CTP:phosphocholine cytidylyltransferase) in the CDP-choline pathway was increased, not decreased, in these cell lines as judged by immunoblot analysis and enzymic activity. Conversion of phosphatidylethanolamine to PC was enhanced in CHO cells that expressed PEMT2 activity. PC mass was not increased in the transfected compared with the control cells. The rate of PC catabolism made by either the CDP-choline or methylation pathways was unaffected by PEMT2 expression. We conclude that expression of PEMT2 in CHO cells does not down-regulate, but rather enhances, the expression of CTP:phosphocholine cytidylyltransferase.